The relevance of the use of electroencephalography and audiometry for the diagnosis of drug-related nervous system complications in patients with multi-drug resistant pulmonary tuberculosis during the main course of chemotherapy - V.I. Ignatieva; T.M. Martsinyuk; V.A. Svyatnenko; G.L. Gumeniuk (Civic Union "Communicable Diseases Intensive Care Association", 2018)
PURPOSE. To analyze the relevance of introduction of modern diagnostics methods for the evaluation of drug-related complications that affect the nervous system in TB treatment practice. MATERIALS AND METHODS. We have analyzed the literature data regarding the problem of diagnosing drug-related complications that affect the nervous system in patients with multi-drug resistant pulmonary tuberculosis during the main course of chemotherapy. RESULTS. According to the results of the analysis, it was revealed that today in the TB practice there is over- or under-diagnosing of drug-related complications from the part of nervous system in patients with multi-drug resistant pulmonary tuberculosis during the main course of chemotherapy, which is due to the lack of technical possibilities of control and the need to get conclusions from specialists with narrow expertise - otolaryngologists, ophthalmologists and neuropathologists. CONCLUSIONS. The lack of data on the prevalence of drug-related nervous system complications is due to the possibility of their detection only with the help of specific technical means of control and on the basis of the conclusions of narrow specialists. The wide introduction of electroencephalography using evoked potentials and audiometry in TB practice will allow obtaining objective data on prevalence, carrying out clear differential diagnostics, monitoring the development of such complications, as well as providing timely treatment within the required amount.